Describing nurses’ awareness of biological risk in delivering care for renal-dialysis patients: an Italian pilot survey: Nurses’ awareness about biological risk in dialysis setting - Magnaghi, Cristiano; Caruso, Rosario; Brioni, Elena; Apuzzo, Luigi; Galli, Marilena; Massari, Cristiano; Del Pin, Marco; Magon , Arianna; Vezzoli, Giuseppe; Villa, Giulia; Manara, Duilio (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of work. Despite national descriptions of awareness, knowledge, and perceptions about the exposure to the biological risk among nurses employed in renal-dialysis care are pivotal to increase work safety, there is a paucity of data on these descriptions in the Italian context. This study aimed at describing Italian nurses’ awareness and knowledge about biological risk in delivering care for renal-dialysis patients, and their experiences of biological accidents.Methods. A pilot survey using cross-sectional data collection and convenience sampling procedure. 124 nurses were enrolled receiving a 7-item questionnaire: Questions 1, 2, and 7 were referred to the awareness about educational learning needs, questions 3 and 4 explored nurses’ knowledge about biological risk, questions 5 and 6 collected accident-related information.Results. Overall, nurses’ awareness and knowledge about biological risk appeared almost limited. Surprisingly, 52% of the enrolled nurses experienced a biological accident, and 29.5% reported to know colleagues who developed work-related disease after a biological accident. We found positive significant associations between awareness and knowledge.Conclusions. This pilot study highlighted the need to further describe Italian nurses’ awareness and knowledge about biological risk in delivering care for renal-dialysis patients, as well as the need of up-to-date epidemiological description about biological accidents. Accordingly, future studies are highly recommended to provide robust evidence aimed at supporting policy makers, educators, clinicians, regulators, and managers.